Penerapan Strategi Pembelajaran Experiential Learning dalam Meningkatkan Hasil Belajar Siswa pada Kelas XI SMA Negeri 1 Pangkajene - Muhammad Syahril Sabirin; Muliadi Muliadi; Umar Mansyur (Journal on Education, 2024)
This study aims to improve student learning outcomes, the application of experiential learning strategies in learning can improve the writing skills of grade XI F IPA SMA Negeri 1 Pangkajene students who are expected. This type of research is Classroom Action Research (PTK). Classroom action research aims to improve the quality or problem solving in the subjects studied and observe the level of success or consequences of his actions, to then receive additional actions that are refinements of actions or adjustments to conditions and situations in order to achieve better results. In the Precycle, the average score of students is 60 and those who reach KKM are 6 people or 19%. In cycle 1, the average score of students is 70 and those who achieve KKM scores are 18 people or 58%. The average score of students in cycle 2 increased by 83 and those who reached KKM were 29 students or 94%. Based on the results of the research and discussion above, it can be concluded that the process of implementing experiential learning strategies can improve learning outcomes in writing short story texts in grade XI F IPA SMA Negeri 1 Pangkajene students. From the research data conducted during the Precycle stage to cycle 2 showed different results. Where each cycle shows an increase in learning outcomes in students.